Puzzle górnośląsko-zagłębiowskie. Społeczne uwarunkowania funkcjonowania Górnośląsko-Zagłębiowskiej Metropolii - Bierwiaczonek, Krzysztof (Człowiek i Społeczeństwo, 2023)
Górnośląsko-Zagłębiowska Metropolia (Metropolis GZM) is the first metropolitan association operating in Poland according to the Act. It includes 41 municipalities of various sizes, administrative statuses and affiliations to cultural regions. This situation poses a significant challenge for integrating municipalities and residents of the Metropolis GZM. The article presents an analysis of selected social dimensions of intra-metropolitan diversity, taking into account the size structure of the municipality and the cultural heterogeneity of the Metropolis GZM. The empirical point of reference was a secondary analysis of data from original and co-authored research conducted in the metropolitan area in the last ten years and publicly available data from public sources. Their analysis revealed, on the one hand, the durability of symbolic boundaries (including phantom ones), the emerging new divisions (between new and rooted inhabitants of peripheral metropolitan municipalities), and, on the other hand, the deepening functional integration of the municipalities and inhabitants belonging to Metropolis GZM.